Accounts Receivable Overdue and Market Dynamics: A Case Study - Niek Stam; Wim Westerman (The Central European Review of Economics and Management (CEREM), 2018)
Aim: This study aims to find out which market dynamics are currently relevant for accounts receivable levels (specifically overdues), and how lessons learned can be used by credit management.Design / Research methods: The unique research strategy is characterised as a single case study with design elements at two country units of a company to be named FEED. The classification and overview of relevant market dynamics provide valuable insights for determinants and intercompany differences in receivables, and whether these arise at the country or market level.Conclusions / findings: The classification and overview of relevant market dynamics provide valuable insights for determinants and intercompany differences in receivables, and whether these arise at the country or market level.Originality / value of the article: The findings suggest adjustments of the literature in that the interest rate is currently not a relevant factor. Moreover, instead of focussing on costs of capital, an emphasis on default risk is more applicable nowadays, and hence researchers should focus on overdue instead of on receivables in general.
Keywords: G30; Q13; 330; Accounts Receivable; Overdue; Market Dynamics; Case Study